The impact of legislation on higher education institutions (Journal of Human Sciences, 2020)
This study aims to study the issue of the impact of legislation on the outcomes of higher education, because the relationship between the good formulation of legislative texts and institutions of higher education is a clear relationship in that legal legislation constitutes the main enabler through which the policies and general objectives of countries in the field of education can be transformed into legal rules that are consistent and consistent with each other. Some facilitate their implementation and enable individuals to invoke them against the state on the one hand, and against each other on the other.